Local genetic structure of a montane herb among isolated grassland patches: implications for the preservation of genetic diversity under climate change. Issue 3 (11th April 2013) - Ernst, Anna; Sauer, Jan; Wittig, Rüdiger; Nowak, Carsten
Abstract: Habitat loss, fragmentation of meadow patches, and global climate change (GCC) threaten plant communities of montane grasslands. We analyzed the genetic structure of the montane herb Geranium sylvaticum L. on a local scale in order to understand the effects of habitat fragmentation and potential GCC impacts on genetic diversity and differentiation. Amplified fragment length polymorphism (AFLP) fingerprinting and cpDNA sequencing was performed for 295 individuals of 15 G. sylvaticum populations spanning the entire distribution range of the species in the Taunus mountain range in Germany. We found patterns of substantial genetic differentiation among populations using 150 polymorphic AFLP markers (mean F ST = 0.105), but no variation in 896 bp of plastid DNA sequences. While populations in the center of their local distribution range were genetically diverse and less differentiated, higher F ST values and reduced genetic variability was revealed for the populations at the low‐altitudinal distribution margins. Projections of GCC effects on the distribution of G. sylvaticum in 2050 showed that GCC will likely lead to the extinction of most edge populations. To maintain regional genetic diversity, conservation efforts should focus on the diverse high‐altitude populations, although a potential loss of unique variations in genetically differentiated peripheral populations could lower the overall genetic diversity and potentially the long‐term viability in the study region. This study documents the usefulness of fine‐scale assessments of genetic population structure in combination with niche modeling to reveal priority regions for the effective long‐term conservation of populations and their genetic variation under climate change.